2020
DOI: 10.3390/ijms21072479
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Astrocyte Autophagy to Systemic Metabolism

Abstract: Autophagy is an essential mechanism to maintain cellular homeostasis. Besides its role in controlling the quality of cytoplasmic components, it participates in nutrient obtaining and lipid mobilization under stressful conditions. Furthermore, autophagy is involved in the regulation of systemic metabolism as its blockade in hypothalamic neurons can affect the central regulation of metabolism and impact body energy balance. Moreover, hypothalamic autophagy can be altered during obesity, one of the main alteratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 104 publications
1
27
0
1
Order By: Relevance
“…But under standard conditions most neuronal ACSS2 is already localized to the nucleus. Since PDK2 and NF-κB play pro-inflammatory and pro-aging roles in glial cells, the AMPK-ACSS2-TFEB pathway likely stimulates autophagy in hypothalamic astrocytes to decrease inflammation and slow the rate of aging [ 448 ]. Further research is needed (1) to elucidate the mechanisms through which ACSS2 mediates these opposing effects on autophagy in different tissues, (2) to decipher the mechanisms through which HDAC inhibitors delay aging, (3) to determine the mechanisms through which CR increases CBP expression in the hypothalamus, (4) to determine if hypothalamic CBP-mediated histone acetylation promotes longevity in mammals by inducing the UPR mt , and (5) to determine if GTA or other acetate-releasing compounds that increase brain histone acetylation can mimic the anti-aging effects of HDAC inhibitors and CR.…”
Section: Discussionmentioning
confidence: 99%
“…But under standard conditions most neuronal ACSS2 is already localized to the nucleus. Since PDK2 and NF-κB play pro-inflammatory and pro-aging roles in glial cells, the AMPK-ACSS2-TFEB pathway likely stimulates autophagy in hypothalamic astrocytes to decrease inflammation and slow the rate of aging [ 448 ]. Further research is needed (1) to elucidate the mechanisms through which ACSS2 mediates these opposing effects on autophagy in different tissues, (2) to decipher the mechanisms through which HDAC inhibitors delay aging, (3) to determine the mechanisms through which CR increases CBP expression in the hypothalamus, (4) to determine if hypothalamic CBP-mediated histone acetylation promotes longevity in mammals by inducing the UPR mt , and (5) to determine if GTA or other acetate-releasing compounds that increase brain histone acetylation can mimic the anti-aging effects of HDAC inhibitors and CR.…”
Section: Discussionmentioning
confidence: 99%
“…In hypoxia-ischemia-induced brain injury, Beclin-1 has been observed to colocalize with neurons but not GFAP-positive cells [90]. A recent study has also reported that hypothalamic astrocyte autophagy regulates obesity and systemic metabolism [91]. The antidepressant fluoxetine has also been suggested to promote autophagic flux and enhance autophagosome fusion in astrocytes [92].…”
Section: Discussionmentioning
confidence: 98%
“…Glial fibrillary acidic protein (GFAP), with molecular weight 50 kDa, encoded by the human GFAP gene found on chromosome 17q21, is a class-III intermediate filament that is expressed by astrocytes in the central nervous system [ 227 , 228 ]. GFAP is an astrocyte-specific biomarker that has a role in cell mobility and migration, proliferation and astrocyte transformation, vesicle transport and autophagy, and astrocyte–neuron interactions [ 229 , 230 ].…”
Section: Inflammation and Glial Activation In Alzheimer’s Diseasementioning
confidence: 99%